Phylogenetic Analysis of Groupers at Labuhan Lombok Based on CO1 Gene - Baiq Endang Kurnia Ramdhani; Mahrus Mahrus; Lalu Zulkifli (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Groupers (family Serranidae) are high-value reef fish that are often prone to misidentification due to their morphological similarities. This research examined the phylogenetic relationships of grouper species landed at the Pondok Sampan Fish Landing Site in Labuhan Lombok using the Cytochrome Oxidase Subunit I (CO1) gene. One specific sample (K5) was analyzed to verify its taxonomic status. DNA isolation was performed through the CTAB technique, followed by PCR amplification and sequencing. Morphological identification initially suggested the sample belonged to the genus Epinephelus. However, molecular results showed that K5 is Aethaloperca rogaa (100% similarity). The phylogenetic analysis was conducted using the Neighbor-Joining approach with 10,000 bootstrap iterations and the Kimura 2-Parameter model in MEGA XI, which placed the specimen within a monophyletic group alongside A. rogaa sequences from Egypt, showing a genetic distance of 0.00. The nucleotide composition (T: 29.8%, C: 27.3%, A: 25.5%, G: 17.4%) was identical to the reference sequence, confirming the anti-G bias typical of teleost mitochondrial DNA. This research illustrates the critical importance of DNA barcoding to correct morphology-based misclassifications. It emphasizes the need for genetic confirmation in fisheries diversity evaluations and in the sustainable management of grouper populations across the Indo-Pacific.